2007
DOI: 10.1186/1479-5876-5-70
|View full text |Cite
|
Sign up to set email alerts
|

Association between long-term neuro-toxicities in testicular cancer survivors and polymorphisms in glutathione-s-transferase-P1 and -M1, a retrospective cross sectional study

Abstract: Background: To assess the impact of polymorphisms in Glutathione S-transferase (GST) -P1, -M1, and -T1 on self-reported chemotherapy-induced long-term toxicities in testicular cancer survivors (TCSs).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(76 citation statements)
references
References 40 publications
1
69
1
5
Order By: Relevance
“…23,24 Additionally, the minor allele of XPC Lys939Gln could be associated with higher risk of ototoxicity, although the limited number of patients included in the analysis does not permit definitive conclusions. Although a recent paper 25 has reported an association of polymorphisms in the drug metabolism gene, GSTP1, with ototoxicity in testicular cancer survivors, 25 no studies relating XPC variation with hearing impairment have been published to date. A possible explanation for our observed association could be that Lys939Gln may reduce the activity of XPC, and thus its DNA repair capacity.…”
Section: Dna Repair Gene Polymorphisms In Osteosarcoma Treatmentmentioning
confidence: 99%
“…23,24 Additionally, the minor allele of XPC Lys939Gln could be associated with higher risk of ototoxicity, although the limited number of patients included in the analysis does not permit definitive conclusions. Although a recent paper 25 has reported an association of polymorphisms in the drug metabolism gene, GSTP1, with ototoxicity in testicular cancer survivors, 25 no studies relating XPC variation with hearing impairment have been published to date. A possible explanation for our observed association could be that Lys939Gln may reduce the activity of XPC, and thus its DNA repair capacity.…”
Section: Dna Repair Gene Polymorphisms In Osteosarcoma Treatmentmentioning
confidence: 99%
“…In a study by Oldenburg et al, GSTP1 rs1965 was significantly associated with cisplatininduced ototoxicity in adult testicular cancer survivors (Table S4) 36 . However, this association did not achieve statistical significance in an extended patient cohort 37 . Rednam et al reported an opposite effect of GSTP1 rs1965 on cisplatin-induced hearing loss in a pediatric medulloblastoma cohort 42 .…”
Section: Gluthathione S-transferases (Gsts)mentioning
confidence: 97%
“…Overall, evidence regarding an effect of GSTP1 rs1695 on ototoxicity is thus inconsistent (Table S4) (+ evidence). Finally, associations with cisplatin-induced ototoxicity have also been reported for GSTM1 (Table S5) 36,37 and GSTT1 (Table S6) 39 . However, numerous other studies have not replicated these associations 15,[35][36][37][38]41,42 (+ evidence).…”
Section: Gluthathione S-transferases (Gsts)mentioning
confidence: 99%
See 2 more Smart Citations